Differences in morphometry and seed germination of Croton guatemalensis (Euphorbiaceae), from wild populations of the Zoque Forest, Chiapas, Mexico - Pozo-Gómez, Dulce María; Orantes-García, Carolina; Rioja-Paradela, Tamara Mila; Moreno-Moreno, Rubén Antonio; Farrera-Sarmiento, Oscar (Instituto de Ecología, A.C., 2018)
Background and Aims: Croton guatemalensis is a native species that is used locally and plays an important role in the traditional medicine of people of the rural comunities of the Zoque Forest, Chiapas, Mexico. Currently it is protected by the NOM-059-SEMARNAT-2010 under “Special Protection”. The objectives of this research were to evaluate the morphometry, viability, health and germination of seeds collected from wild populations in four Protected Natural Areas of the Zoque Forest, Chiapas; and generate basic information that will allow the development in the future local programs or projects of conservation, restoration and forest management of the species, in order to reduce the impact on wild populations.Methods: From November 2016 to October 2017, plant material was collected to corroborate the taxonomic identification of Croton guatemalensis, and fruits and seeds to determine, under a random design, the size (length × thickness), weight, percentage of viability, health and germination of the seeds. Due to the abnormality of the data, the comparison and determination of the statistical differences between areas was carried out by Kruskal-Wallis and Mann-Whitney analyses, in the software R 3.24.Key results: The results indicate that there are statistically significant differences between the four collection zones. The most contrasting results were present in the Area Subject to Ecological Conservation La Pera and Protected Forest Area Vedada Villa de Allende. In the first, the seeds had larger size (5.13±0.06 × 3.26±0.06 mm), high percentage of health, viability and final germination (98±2.16, 98±2.30, 98±3.84%, respectively), while in the second, the seeds were smaller (4.63±0.09 × 2.69±0.08 mm), they obtained 68±6.65% of health, 19±5.03% of viability and 6±3.84% of final germination.Conclusions: The present study provides reproductive information essential for the generation of strategies for conservation, restoration and forest management of the species Croton guatemalensis.